Critical insights into modern slavery : case of debt bonded labour in Indian brick kilns : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management at Massey University, Palmerston North, New Zealand - Nazir, Omer (Massey University, 2021)
‘Modern slavery,’ an umbrella term used to describe many forms of severe exploitations, has sparked a growing interest in management and organisation research. This has led to the acknowledgement of both the illegitimacy and scale of modern slavery, resulting in new legislations (e.g. the Modern Slavery Act 2015 in the United Kingdom) urging businesses to eradicate modern slavery from their supply chains. The efforts of academia in promoting these laws indicate that the interventions are typically viewed as enlightened and founded in scientific research. Yet, as an International Labour Organisation report noted, more people are now categorised as slaves in modern times than was the case when slavery was legal (ILO, 2019). This study takes a critical step back from ‘how’ modern slavery can be eradicated to ‘why’ do we understand modern slavery the way we do and what has sustained such insidious practice. Adopting a Marxian ontology and Foucauldian epistemology and drawing from ‘exploitations’ based theoretical framework, this study uses a case-study approach to examine the ‘form’ and ‘formation’ of modern slavery, with a focus on debt bondage, in the Indian brick kiln industry. The research design involved multi-method analyses, comprised of discourse analysis, visual (film) analysis, interviews and observations, and autoethnography. The results from this study call into doubt the candour of the widely accepted notion of modern slavery being an individualised relation between a master and a slave – a form that it took in the nineteenth century. Instead, this thesis suggests thinking differently about modern slavery such that the form and formation of debt bondage are placed in the wider context of everyday life in the midst of neoliberal regimes. In that vein, the thesis concludes that modern slavery is not simply an individualised relation between a master and a slave, but a complex phenomenon produced by everyday interactions, for example, in relation to food, family, love or responsibility; and sustained by neoliberal logics that serve as the basis of particular regimes of truth.
Keywords: Brickmakers; Brickmaking; Peonage; Slavery; India; 350504 Industrial and employee relations